Recommendations to Enhance the Educational Experience of Aboriginal Social Work Students - Artemis Fire (Critical Social Work, 2019)
It is troubling that universities continue to have too few Aboriginal students, especially in social work, because of both the historical harm done through social work and the high percentage of Aboriginal clients in many areas of practice. This paper looks at ways post-secondary institutions can work towards reconciliation with First Nations communities. The inside-out model of self-reflective transformation of the institution is examined, focusing on: removing barriers to accessing post-secondary education, providing support, epistemology and curriculum, and indigenizing social work education. It concludes with a practical list of recommendations.